Management Control Systems and Joint Venture Performance: A Contingent Approach to Parent?s Experience - Marcela Porporato (Journal of Accounting, Business and Management (JABM), 2012)
This study contributes to the understanding of management control systems (MCS) use in international joint ventures (IJVs) by proposing a contingent framework. In particular this study is interested in assessing the use of MCS information to overcome internal uncertainty of operating an IJV (Lu and Hebert, 2005). A path model was applied to data from 35 50/50 IJVs in the automotive parts industry. The results indicate that the intensity of use of MCS improves IJV performance confirming that MCS are used to reduce uncertainty in Galbraith (1973) terms. Uncertainty is reduced because each partner, according to their prior experience, uses different sets of information with different intensities which in turn improves IJV performance.